STRATEGY TO ENHANCE SOCIAL ENTREPRENEURSHIP THROUGH THE USE OF NEW MEDIA WITHIN MALAYSIA GLOBAL INNOVATION AND CREATIVE CENTRE (MaGIC) - Munirah Mohd Jidi; Nur Faithzah Jamian; Erratul Shela Eshak; Norlida Zakirai@Zakaria (International Journal of Accounting, Finance and Business, 2021)
This study is being conducted to determine a strategy for enhancing socialentrepreneurship within Magic by digital media. The aim of this study was to determine therelationship between the use of social media and the growth of social entrepreneurship throughqualitative analysis. The information for this study was gathered from entrepreneurs who wereselected to meet the criteria. Two entrepreneurs have been chosen to collect data for theresearch. Data is collected through an interviewing process that is focused on questions thathave been created in accordance with the study purpose and research query. The findingsshows that both informants stated that social media is very significant in developing socialentrepreneurship. The findings also show that social entrepreneurship and improving livingstandards are related. This research's contribution is that it provides entrepreneurs with abrilliant idea for expanding their business using social media and considers solutions toproblems relevant to social entrepreneurship.